The Question of the Hasty Mass-Exodus of Jews from Yemen between 1949-1950 (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
What was the catalyst behind the rushed exodus of tens of thousands of Jews fromYemen during the second and third phase of Operation Magic Carpet? What led tothe exit that was unique in scope and speed compared to former waves of migrationfrom Yemen, and which took place in contrast to the predictions of both the Britishand the organizers of the Aliyah, who expected the Jews to leave gradually over aperiod of several years?So far, this phenomenon was not emphasized within the research, and wasexplained away as the result of a combination of circumstances in real time,religious-messianic motives, and the practical advantages embedded within thefoundation of the State of Israel. In this article, I will show that these explanationsstill leave a gap in our understanding of the broader picture of this mass immigrationof Jews from Yemen, and that a satisfactory explanation for the question has yetto be provided.I will turn a spotlight on the harsh events that took place in Yemen during theyear and a half before this wave of immigration, and examine their influence onthe feelings of Jews, their living conditions, and their sense of security. A newreading of existing testimonies, including letters written by Yemenite Jews duringthe fact, as well as later testimonies, tells the story of these immigrants and of theirdeparture and suggests that alongside the familiar push and pull factors, migrationfrom Yemen also had clear elements of escape.I suggest that the series of difficult events that preceded migration and theweakening of the Imam's protection spread continuing feelings of anxiety, anduncertainty among the Jews of Yemen, shaking the very foundations of their senseof security and pushing them toward extensive and urgent migration from Yemento Israel – the only state that offered them sanctuary and hope for the future.
Keywords: The Great Aliyah; Yemenite Jews; Exodus of Jews from Yemen; The Magic Carpet; Yemenite Aliyah; Al Kanfei Nesharim; the Assassination of Imam Yahya